Stellar evolution concepts and the dissemination of knowledge in Astronomy (Research, Society and Development, 2020)
In this work, an information booklet on the topic of Stellar Evolution was prepared, based on a bibliographic review of the literature in the field, aiming to create subsidies for the development of this science at different levels of knowledge. The booklet, which is intended to be used by teachers and students of Basic Education, was designed as a way of contributing to the shortage of teaching materials in this field. Here, it is presented the main scientific concepts worked on the booklet to support teachers and students, as well as comments on the experience with the presentations of lectures and workshops based on the booklet, in educational environments, in the Brazilian city of Marabá, in the state of Pará, as a way of disseminating and encouraging Astronomy in the region. It was noticed that the school community, in general, has a great interest in the learning of Astronomy, which contrasts with the scarcity of didactic materials and knowledge opportunities in the field. It is expected that more proposals for teaching materials, as well as applications of activities in Astronomy, will be developed, in order to disseminate such science in the school environment, and also in the general community.